Expert Opinion on Fixed Dose Combination of Dapagliflozin Plus Sitagliptin for Unmet Cardiovascular Benefits in Type 2 Diabetes Mellitus - Soumitra Ray; J Ezhilan; Rajiv Karnik; Ashish Prasad; Rajashree Dhar (Journal of Diabetology)
Abstract Type 2 diabetes mellitus (T2DM) is known to be associated with macrovascular (coronary heart disease, stroke, and peripheral arterial disease) and microvascular complications (diabetic kidney disease, retinopathy, and peripheral neuropathy). The coexistence of T2DM with established/risk of atherosclerotic cardiovascular disease (ASCVD), heart failure (HF), or chronic kidney disease confers a poor prognosis, and management can be challenging. Guidelines recommend clinicians to consider CV/HF risk, renal/hepatic risk, and other comorbidities while choosing an antidiabetic regimen. The fixed dose combination (FDC) of sodium-glucose cotransporter-2 (SGLT2) inhibitors and dipeptidyl peptidase-4 (DPP-4) inhibitors provides both glycemic and pleiotropic effects, including lower risk of hypoglycemia, lower rates of genitourinary tract infections, and weight neutrality. Based on CV risk, including HF, the combination of SGLT2i and DPP4i may be preferred over other conventional therapies (those with no CV benefit) in cases of established CV disease and/or HF risk. The Indian expert consensus group discussed the literature, clinical benefits, and the role of the FDC of Dapagliflozin and Sitagliptin for the unmet cardiovascular benefits in T2DM patients. This practical guidance document would support general physicians, endocrinologists, diabetologists, cardiologists, and nephrologists in selecting the appropriate regimen for superior patient outcomes.